Cardiac 123I-MIBG Scintigraphy in Neurodegenerative Parkinson Syndromes: Performance and Pitfalls in Clinical Practice - Skowronek, Cornelia; Zange, Leonora; Lipp, Axel (Frontiers in Neurology, 2019)
Purpose: Cardiac [123I]metaiodobenzylguanidine scintigraphy (123I-MIBG), reflecting postganglionic cardiac autonomic denervation, is proposed for early detection of Parkinson’s disease (PD; reduced tracer uptake) and separation from Multiple System Atrophy (MSA; preserved tracer uptake). However, several recent studies report on frequent unexpected 123I-MIBG results in PD and MSA. We sought to determine, whether 123I-MIBG is feasible to discriminate PD from MSA in unselected geriatric patients in clinical practice. Materials and Methods: We screened consecutive patients, that underwent 123I-MIBG and 123I-FP-CIT SPECT for diagnostic reasons. Delayed 123I-MIBG uptake and 123I-FP-CIT SPECT result composed nuclear medical diagnosis. Clinical diagnosis was based on a two-stage clinical assessment: comprehensive baseline (including autonomic testing and additional neuroimaging) and confirmatory clinical follow-up. Results: 28 patients with clinical diagnosis of PD (N=11), MSA (N=9) and Essential Tremor (ET, N=8) were identified. In one third (9/28) nuclear medical diagnosis deviated from clinically suspected syndrome. Visual interpretation of 123I-MIBG identified two cases (MSA and ET) with indeed normal 123I-MIBG uptake. Detailed review of clinical phenotypes provided only in two cases (PD and ET) an adequate explanation (correction of initial diagnosis and confounding drug history) for unexpected 123I-MIBG. In conclusion, 123I-MIBG did not match initial clinical phenotype in 27% PD, 44% MSA and 25% ET patients. Conclusion: Predictability of 123I-MIBG based nuclear medical diagnosis for individual cases and thus, feasibility in routine clinical practice is limited. Our data emphasize clinical verification of 123I-MIBG results on an individual basis in clinical routine.